2017
DOI: 10.3892/etm.2017.4650
|View full text |Cite
|
Sign up to set email alerts
|

Kanglaite inhibits the expression of drug resistance genes through suppressing PVT1 in cisplatin-resistant gastric cancer cells

Abstract: Abstract. Kanglaite (KLT) was shown to alleviate the development of multidrug resistance (MDR) clinically. The purpose of this study is to examine the mechanism of KLT for chemotherapy resistance in gastric cancer cells involving the regulation of MDR-related proteins. The cisplatin-resistant BGC823/DPP and SGC7901/DDP cells were treated with 1, 2.5 and 5 µl/ml of KLT for 24, 36 and 48 h. Cell Counting Kit-8 (CCK-8) assay and flow cytometry were performed to detect the cell viability and cell apoptosis, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…131,132 And in the prescription of drug resistance in gastric cancer, up-regulating PVT1's expression would raise the expression of p-glycoprotein, MRP, mTOR and HIF-1α to induce multidrugresistance, while inhibiting PVT1's expression would reverse cell resistance to cisplatin. 133,134 Other studies have shown that down-regulating the expression of LEIGC in gastric cancer cells could enhance the resistance to 5-fluorouracil via regulating the EMT process, which suggested LEIGC could be a suppressor lncRNA in gastric cancer. 135 Further studies have found that the target site of lncRNA MRUL is close to p-glycoprotein, and the expression of MRUL is higher in drug-resistance cells.…”
Section: Lncrnas In Drug Resistance Of Gastric Cancermentioning
confidence: 99%
“…131,132 And in the prescription of drug resistance in gastric cancer, up-regulating PVT1's expression would raise the expression of p-glycoprotein, MRP, mTOR and HIF-1α to induce multidrugresistance, while inhibiting PVT1's expression would reverse cell resistance to cisplatin. 133,134 Other studies have shown that down-regulating the expression of LEIGC in gastric cancer cells could enhance the resistance to 5-fluorouracil via regulating the EMT process, which suggested LEIGC could be a suppressor lncRNA in gastric cancer. 135 Further studies have found that the target site of lncRNA MRUL is close to p-glycoprotein, and the expression of MRUL is higher in drug-resistance cells.…”
Section: Lncrnas In Drug Resistance Of Gastric Cancermentioning
confidence: 99%
“…Thus, enhanced MRP1 expression in GAC cells obtained from naïve patients after cisplatin treatment and in the cisplatin-resistant GAC cell line KATOIII/DDP has been found [22]. Indirect evidence further supports that MRP1 is involved in cisplatin resistance [23,24]. MRP1 overexpression in vitro reduced the cytotoxic effect of doxorubicin, whereas tanshinone IIA (an abietane diterpene) potentiated doxorubicin effect, even in resistant GAC cells, by MRP1 inhibition [25].…”
Section: Export Pumps (Moc-1b)mentioning
confidence: 85%
“…It is also the first Chinese medicine approved by the US Food and Drug Administration, and has been used as a biphasic broad-spectrum antitumor drug in clinical trials in the United States. [ 16 , 17 ] Millions cancer patients in more than 2000 hospitals in China have been treated with Kanglaite injection. [ 18 ] It has been widely used for the treatment of Pancreatic cancer, [ 19 , 20 ] lung cancer, [ 21 , 22 ] breast cancer, [ 23 ] colorectal cancer, [ 24 ] hepatocellular carcinoma, [ 25 ] and GC.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 , 27 ] Researches showed that Kanglaite injection could effectively reverse multiple-drug resistance in cancer cells and enhance the sensitivity of tumor cells to chemotherapeutic drugs. [ 17 , 27 29 ]…”
Section: Introductionmentioning
confidence: 99%